2022
DOI: 10.1002/jcla.24554
|View full text |Cite
|
Sign up to set email alerts
|

Analytical and clinical performance of different platforms simultaneously detecting 15 antinuclear antibodies

Abstract: Background: Antinuclear antibodies (ANAs) are invaluable biomarkers for the diagnosis of autoimmune diseases (AIDs). This study aims to compare the performances of line immunoassay (LIA), multiplex bead-based flow fluorescent immunoassay (MBFFI), and magnetic bar code immunofluorescence assay (MBC-IF) to detect ANA-Profile-15S. Methods: In total, 184 samples from AID patients and 50 healthy controls (HCs) were collected. Fifteen ANAs (anti-dsDNA, nucleosome, histone, Sm, PCNA, ribosomal-P, SS-A/Ro52, SS-A/Ro60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…However, sensitivity, specificity, positive predictive value, negative predictive value, and diagnostic accuracy of these diagnostic approaches may vary, and combinations of methods are recommended in clinical settings [89]. Using sera specimens of 184 autoimmune disease patients and 50 controls, Qin et al evaluated the analytical and clinical performance of line immunoassay, multiplex beadbased flow fluorescent immunoassay, and magnetic bar code immunoassay in detection of antinuclear antibodies, including those targeting Ro60 and Ro52; they found that the three assays showed good agreement [90]. Diagnostic accuracy is an important parameter in autoantibody detection, requiring consistent refinement of validation assays.…”
Section: Ro60 Autoantibodies In Diagnosis and Monitoring Of Autoimmun...mentioning
confidence: 99%
“…However, sensitivity, specificity, positive predictive value, negative predictive value, and diagnostic accuracy of these diagnostic approaches may vary, and combinations of methods are recommended in clinical settings [89]. Using sera specimens of 184 autoimmune disease patients and 50 controls, Qin et al evaluated the analytical and clinical performance of line immunoassay, multiplex beadbased flow fluorescent immunoassay, and magnetic bar code immunoassay in detection of antinuclear antibodies, including those targeting Ro60 and Ro52; they found that the three assays showed good agreement [90]. Diagnostic accuracy is an important parameter in autoantibody detection, requiring consistent refinement of validation assays.…”
Section: Ro60 Autoantibodies In Diagnosis and Monitoring Of Autoimmun...mentioning
confidence: 99%